Kala azar in Pregnancy - Miah, MT; Ayaz, FM; Maniruzzaman, M; Ahasan, MN; Bari, S; Mawla, SM; Mahbub, MS; Khan, AI (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):529-32 The abstract of this article is available on the PubMed website